Boris Yeltsin: A Revolutionary Life - Aron L. (Leon) (London: HarperCollins Publishers, 2000)
The first freely elected head of state in Russia's 1,000-year history, Boris Yeltsin ended Soviet military occupation of Eastern Europe, disolved the Russian domestic empire, introduced the free-market economy and private property and, most importantly, forget and presided over the most open and tolerant regime Russian has ever known.
(NP(B/20286s
+Map
+Photos
Keywords: the bellwether -- in power -- the storm